IbM FOR EMPOWERING OF A TYPICAL CAKE VELLAGE IN SURABAYA - Zakariya .; Agus Sukristyanto; Kunto Inggit Gunawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
Micro business â€œAAâ€ and â€œRahayuâ€ are a businessman engaged in the field of making wet cakes and pastries. Two entrepreneurs have been getting coaching Disperindag city of Surabaya and two micro enterprises crowned as a village cake. the problems that are still faced by these two entrepreneurs are: not many have the means of production to fulfill their business activities; the ability to make bread is still simple; have not been able to make good bookkeeping and have not utilized online marketing in their business activities. The activity method used by this activity are: Â Provide the right means of production, among others: toaster or oven machine, mixer, blender, and other supporting tools: Â Cake-making training such as:Â Sus Fla, Sus Fla buah, Sus Rogut, Cum-cum, Panada, Bongko menthuk dan risol mayo,dadar gulung, lumpur kentang, lemper, kroket, cake basah and aneka rotimanis cake: Â Business bookkeeping training and mareketing online training. The result community empewering have been achieved are: Â Micro business â€œAAâ€ and â€œRahayuâ€ have production equipment and ever more tools production.Â They have been accustomed to doing business bookkeeping and they have known the use of online marketing. The impact is all they have been an increase in the quantity and quality of production. So that automatically the revenue of their busunees are increased. Â Â Â Keywords:Â Appropriate technology, Cake-making training, Business bookkeeping and mareketing online training